Convolutional neural networks ensembles through single-iteration optimization - Ribeiro, Luiz C. F. [UNESP]; Rosa, Gustavo H. de [UNESP]; Rodrigues, Douglas [UNESP]; Papa, João P. [UNESP] (Springer Nature, 2022)
Convolutional Neural Networks have been widely employed in a diverse range of computer vision-based applications, including image classification, object recognition, and object segmentation. Nevertheless, one weakness of such models concerns their hyperparameters’ setting, being highly specific for each particular problem. One common approach is to employ meta-heuristic optimization algorithms to find suitable sets of hyperparameters at the expense of increasing the computational burden, being unfeasible under real-time scenarios. In this paper, we address this problem by creating Convolutional Neural Networks ensembles through Single-Iteration Optimization, a fast optimization composed of only one iteration that is no more effective than a random search. Essentially, the idea is to provide the same capability offered by long-term optimizations, however, without their computational loads. The results among four well-known datasets revealed that creating one-iteration optimized ensembles provides promising results while diminishing the time to achieve them.
Keywords: Convolutional neural networks; Ensembles; Machine learning; Meta-heuristics; Optimization